2007
DOI: 10.1080/00207540600635250
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing planning and control approaches: market alignment and performance

Abstract: The design of manufacturing planning and control (MPC) systems is a strategic decision for manufacturing operations. In this paper we analyze the interrelationships between the choice of MPC approaches at different hierarchical levels with market requirements and operational performance. These relationships are explored through an extensive survey comprising responses from 128 manufacturing firms. The results show that the choice of MPC approaches, primarily at the sales and operations planning and master sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 25 publications
2
37
1
3
Order By: Relevance
“…The practical managerial implication is that markets with high-volume, standardised products, few variants, and short lead times should be planned and controlled by level, MTS, rate-based, and JIT/lean-type approaches, whereas markets with low-volume, highly customised products, wide product range, and long lead times should be planned and controlled using chase, MTO, time-phased, and MRP-type approaches. Olhager and Selldin (2007) tested this model empirically and found that the choice of approaches at the MPS and S&OP levels has a significant mediating role for operational performance. S&OP fundamentally concerns volume planning, while the MPS is concerned with product mix planning.…”
Section: Erp and Sales And Operations Planningmentioning
confidence: 99%
“…The practical managerial implication is that markets with high-volume, standardised products, few variants, and short lead times should be planned and controlled by level, MTS, rate-based, and JIT/lean-type approaches, whereas markets with low-volume, highly customised products, wide product range, and long lead times should be planned and controlled using chase, MTO, time-phased, and MRP-type approaches. Olhager and Selldin (2007) tested this model empirically and found that the choice of approaches at the MPS and S&OP levels has a significant mediating role for operational performance. S&OP fundamentally concerns volume planning, while the MPS is concerned with product mix planning.…”
Section: Erp and Sales And Operations Planningmentioning
confidence: 99%
“…S&OP is mainly located at tactical level in the hierarchy of planning. However, when this process deals with scenario management, risk assessment (Wallace & Stahl, 2008) or the expansion of capacity (Olhager, et al, 2001) (Olhager & Selldin, 2007) , it has extensions towards the strategic level (Olhager & Rudberg, 2002) (Wallace & Stahl, 2008) (Alexander, 2013).…”
Section: Definition and Scopementioning
confidence: 99%
“…Grimson and Pyke (2007) offered a five-stage framework for helping improve the effectiveness of S&OP processes with close linkages to overall company strategy. Olhager and Selldin (2007) used a survey-based design to analyze the interrelationships between manufacturing planning and control approaches at different levels and operational performance given market requirements. According to Wallace (1999), S&OP focuses on aggregate volumes and product families.…”
Section: Strategic Direction and Production Planning And Control Systemsmentioning
confidence: 99%